PENGEMBANGAN BUKU CERITA ANAK BERBASIS NILAI KARAKTER UNTUK MENINGKATKAN KETERAMPILAN SOSIAL ANAK TK - Listyaningsih, Brigitta Tyas; Vivid Herlina Bate’e; Eny Winarti; Susan Agustina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Children aged 0-6 years, the golden age, are in a critical period that establishes the foundation for their physical, cognitive, social, and emotional development. Early childhood character education plays a significant role in shaping social skills and moral values that will influence children’s future behavior. This study aims to develop a storybook based on character values to improve social skills for kindergarten children, specifically at TK Cahaya Bangsa Utama (Kinderstation), which emphasizes eight personal goals: resilience, communication, collaboration, respect, critical thinking, empathy, adaptability, and ethics. Implementing Researchand Development (R&D) approach which covers a 4D model (Define, Design, Develop, Disseminate) a storybook was developed to fill the needs of children to Findings indicated the storybook developed was effective in helping children comprehend moral and social values, as well as in building communication skills and empathy. The book was beneficial not only as a reading material but also as a tool for in-depth discussions within school and family contexts. The implementation of character-based storybooks was expected to contribute positively to the personality and social skill development of kindergarten children, supporting them to become individuals who are not only of good character but also active contributors to society.